Recent advances in marine biotechnology. vol. 7. Seafood safety and human health. - Fingerman, M. and Health, Human (eds.) (Science Publishers, 2002)
Contents: Machine generated contents note: Preface -- The Contributors -- Brevetoxins: Pharmacology, Toxicokinetics and Detection -- Mark A. Poli -- Azaspiracid, a New Marine Toxin Isolated from Mussels: -- Chemistry and Histopathology -- Emiko Ito and Masayuki Satake -- Enterotoxin of Vibrio cholerae -- Yoshio Iijima and Takeshi Honda -- Exophysiology and Biosynthesis of -- Marine Biotoxins (TTX and PSP) -- Deng-Fwu Hwang and Ya-Hui Lu -- Effects of 4-Aminopyridine in the Treatment -- of Saxitoxin Poisoning -- Fat-Chun Tony Chang, Bernard Benton and David Spriggs -- Development of Commercial Immunoassays -- for Seafood Poisonings -- Paulo Vale -- Highly Sensitive Bioassays for Paralytic Shellfish Toxins -- Franca Guerrini, Clementina Bianchi, Lorenzo Beani, -- Laurita Boni and Rossella Pistocchi -- Bioassays for Paralytic Shellfish Toxins in Crustacea -- Jason Doyle and Lyndon Llewellyn -- Antimicrobial Peptides for Fish Disease Control -- Aleksander Patrzykat and Robert E.W. Hancock -- Fish Protein Hydrolysates and their Potential Use -- in the Food Industry -- Hordur G. Kristinsson and Barbara A. Rasco -- viii MARINE BIOTECHNOLOGY -- Shelf Life Extension and Value Addition of Fishery -- Products: A Critical Evaluation -- Vazhiyil Venugopal -- Recent Advances in Surimi Technology -- Herbert O. Hultin -- DNA-based Diagnostics in Sea Farming -- Carlos R. Osorio and Alicia E. Toranzo -- Index.